Growth, Blood, and Intestinal Indices of Broilers at High Density Pens Provided with Fermented Averrhoa bilimbi Fruit Filtrate - S. Sugiharto; E. Widiastuti; T. Sartono; H. Wahyuni; A. Pratama; T. Yudiarti (Faculty of Animal Science, Bogor Agricultural University, 2022)
The present study investigated the effect of fermented Averrhoa bilimbi fruit filtrate (FABFF) on growth, blood indices, and gut ecology of broilers raised at a high stocking density. Using 378 chicks (14 days of age), the study was arranged based on a factorial design with stocking densities (normal with 9 birds/m2 or high with 18 birds/m2) and treatment with 2% FABFF from drinking water or not as the two factors. Live body weight and feed consumption were registered weekly, while blood and intestinal contents were collected at day 35. Broilers at high density receiving FABFF had the lowest (p<0.05) feed conversion ratio (FCR). Thymus was smaller (p<0.05) in high-stocked broilers receiving only drinking water. Birds administered FABFF had greater (p<0.05) bursa of Fabricius than birds given plain water. The FABFF elevated (p<0.05) serum superoxide dismutase (SOD) levels of broilers. The malondialdehyde levels were higher (p<0.05) in high-stocked broilers given drinking water compared to normal-stocked broilers given drinking water or high-stocked broilers receiving FABFF. Drinking FABFF elevated (p<0.05) the ratio of lactic acid bacteria/coliform in the ileum. Cecal coliform was less (p<0.05) in chicks receiving FABFF than those receiving only water. High-stocked broilers receiving FABFF showed lower (p<0.05) Enterobacteriaceae counts than the other birds. The ratio of lactic acid bacteria/coliform increased (p<0.05) in broilers receiving FABFF. In conclusion, FABFF was capable of maintaining the development of immune organs and improving FCR, antioxidative status, and intestinal microbial balance of broilers stocked at high-density pens.